Facilitating with Ease! - Bens, Ingrid (Tantor Media, Inc., 2019)
Facilitating With Ease! has become the go-to handbook for those who lead meetings, training, and other business gatherings. Packed with information, effective practices, and invaluable advice, this book is the comprehensive handbook for anyone who believes meetings should be productive, relevant, and as short as possible. Dozens of exercises, surveys, and checklists will help transform anyone into a skilled facilitator, and clear, actionable guidance makes implementation a breeze. This new fourth edition includes a new chapter on questioning, plus new material surrounding diversity, globalization, technology, feedback, distance teams, difficult executives, diverse locations, personal growth, meeting management, and much more. With in-depth, expert guidance from planning to closing, this book provides facilitators with an invaluable resource for learning or training. Before you run another meeting, discover the practices, processes, and techniques that turn you from a referee to an effective facilitator. This book provides a wealth of tools and insights that you can put into action today.